Impact of Duodenal Pathology on Oral Drug Bioavailability and Disease Outcomes in Pediatric Crohn's Disease - Rebecca Casini; Carrie A. Vyhlidal; Julia M. Bracken; Ashley K. Sherman; Atif Ahmed; Vivekanand Singh; Veronica Williams; Valentina Shakhnovich (MDPI AG, 2023)
Background: Crohn's disease with upper gastrointestinal tract involvement occurs more often in children than adults and has the potential to interfere with oral drug absorption. We aimed to compare disease outcomes in children receiving oral azathioprine for the treatment of Crohn's disease with (DP) and without (NDP) duodenal pathology at diagnosis. Methods: Duodenal villous length, body mass index (BMI), and laboratory studies were compared in DP vs. NDP during the first year post-diagnosis, using parametric/nonparametric tests and regression analysis (SAS v9.4); the data are reported as the median (interquartile range) or the mean ± standard deviation. Thiopurine metabolite concentration (pmol/8 × 108 erythrocytes) 230-400 was considered therapeutic for 6-thioguanine nucleotides (6-TGN), and >5700 was considered hepatotoxic for 6-methylmercaptopurine (6-MMPN). Results: Twenty-six of the fifty-eight children enrolled (29 DP, 29 NDP) started azathioprine for standard medical care, including nine DP and ten NDP who had normal thiopurine methyltransferase activity. Duodenal villous length was significantly shorter in DP vs. NDP (342 ± 153 vs. 460 ± 85 μm; p < 0.001) at diagnosis; age, sex, hemoglobin, and BMI were comparable between groups. A trend toward lower 6-TGN was observed in the DP vs. NDP subset receiving azathioprine (164 (117, 271) vs. 272 (187, 331); p = 0.15). Compared to NDP, DP received significantly higher azathioprine doses (2.5 (2.3, 2.6) vs. 2.2 (2.0, 2.2) mg/kg/day; p = 0.01) and had an increased relative risk of sub-therapeutic 6-TGN. At 9 months post-diagnosis, children with DP had significantly lower hemoglobin (12.5 (11.7, 12.6) vs. 13.1 (12.7, 13.3) g/dL; p = 0.01) and BMI z-scores (−0.29 (−0.93, −0.11) vs. 0.88 (0.53, 0.99); p = 0.02) than children with NDP. Conclusion: For children with Crohn's disease, duodenal pathology, marked by villous blunting, increased the risk of sub-therapeutic 6-TGN levels, despite higher azathioprine dosing during the first year post-diagnosis. Lower hemoglobin and BMI z-scores at 9 months post-diagnosis suggest the impaired absorption/bioavailability of nutrients, as well as oral drugs, in children with duodenal disease.